Solve the following system of equations.
x^2 + y^2 = 9
x^2 - 3y = 9

- BeccaB003

Solve the following system of equations.
x^2 + y^2 = 9
x^2 - 3y = 9

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- schrodinger

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- BeccaB003

These are the options:
(-3, 0), (3, 0),(-3, 9),(3, 9)
(-3, 9),(-3, 0)
(-3, 0), (0, -3), (3, 0)
(-3, 9)
I am very confused on how to do this problem because there is a 3y and y^2

- anonymous

well since they both = 9 its safe to say they equal each other right @BeccaB003

- anonymous

hello

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

well since they both = 9 its safe to say they equal each other right @BeccaB003

- BeccaB003

I am here. Yes, I suppose they would equal each other.

- welshfella

x^2 + y^2 = x^2 - 3y

- anonymous

so x^2 + y^2 = x^2 - 3y
now solve do -x^2 to get
y^2+-3y

- anonymous

i mean y^2=-3y

- welshfella

subtract x^2 from both sides
y^2 = - 3y

- BeccaB003

@welshfella @DaBest21 But how do you solve with that problem if there is y and y^2?

- welshfella

can you solve that?

- BeccaB003

I thought you used substitution or elimination for problems like this.

- BeccaB003

I don't understand how you would solve for y^2=3y ---they are two different types of variables. you can't combine them or anything.

- welshfella

well i have used elimination - i eliminated x^2

- welshfella

y^2 + 3y = 0
y(y + 3) = 0
y = ?

- welshfella

you factor them as above

- BeccaB003

y(y+3)=0 <---------- is factored

- BeccaB003

I don't know how to simplify that more.

- welshfella

when 2 functions are multiplied together and the result is 0 then either one or the other is zero. I other words there are 2 solutions
y(y + 3) = 0
y = 0 or y + 3 = 0
y = 0 y= -3
0 and -3 are the 2 solutions

- BeccaB003

So then you plug them both into the original equation to find x?

- welshfella

yes plug them into
x^2 - 3y = 9

- welshfella

so when y = -3
x^2 -3(-3) = 9
x^2 + 9 = 9
x^2 = 9-9 = 0
x = 0
so one solution is (0,-3)

- BeccaB003

Okay so, x^2 -3(0) = 9
equals: x^2 = 9
= x = 3

- BeccaB003

So another solution is (3,0)

- welshfella

not quite sqrt x^2 is also -3

- welshfella

right (3,0) is one solution and a third one is (-3,0)

- welshfella

* square root of 9 is also -3

- BeccaB003

How can the square root of 9 be -3?

- welshfella

so the 3rd option is the correct one.

- anonymous

c

- welshfella

3 * 3 = 9
also
-3 * -3 = 9

- BeccaB003

Okay, Thank you so much for your help! :)

- welshfella

yw

Looking for something else?

Not the answer you are looking for? Search for more explanations.